Implementation Guide for SCORE Training. Second (revised) Edition (International Labour Organisation (ILO), 2021)
SCORE is a practical training and in-factory consulting programme that improves productivity and working conditions in SMEs. This step-by-step implementation guide is designed for staff from the ILO and other organizations such as business associations, government agencies and training providers that want to offer SCORE Training to enterprises.